Prisoner's Dilemma on real social networks: Revisited - Sharon M. Cameron; Ariel Cintrón-Arias (Mathematical Biosciences and Engineering)
Prisoner's Dilemma is a game theory model used to describe altruistic behavior seen in various populations. Thistheoretical game is important in understanding why a seemingly selfish strategy does persist and spread throughout apopulation that is mixing homogeneously at random. For a population with structuredetermined by social interactions,Prisoner's Dilemma brings to light certain requirements for the altruistic strategy to become established.Monte Carlo simulations of Prisoner's Dilemma are carried out using both simulated social networks and a datasetof a real social network. In both scenarios we confirm the requirements for the persistenceof altruism in a population.